High-conductivity and high-thermal-conductivity PBT composite material and preparation method thereof
By combining carbon nanostructured material CNS with boron nitride/alumina and bridging with silane coupling agent, the problem of competition between conductive and thermal conductive networks in PBT material was solved, and a PBT composite material with high conductivity and high thermal conductivity was prepared, which is suitable for electronic components and automotive parts.
Patent Information
- Application Number
- CN202511942521.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-22
- Publication Date
- 2026-03-17
AI Technical Summary
Existing PBT materials have low thermal conductivity and high surface resistivity. The high proportion of traditional conductive and thermally conductive fillers significantly affects mechanical properties, and it is difficult for conductive and thermally conductive networks to form a synergistic effect.
A synergistic interpenetrating conductive and thermally conductive network is formed by combining carbon nanostructure material (CNS) with boron nitride/alumina and bridging it with a silane coupling agent. This optimizes the formulation system and solves the problems of competition between conductive and thermally conductive networks and compatibility between fillers and matrix resin.
PBT composite materials with high electrical and thermal conductivity have been developed, exhibiting excellent mechanical properties and suitable for applications such as electronic components and automotive parts.
Smart Images

Figure BDA0005752860710000121
Abstract
Description
Technical Field
[0001] This invention relates to a highly conductive and highly thermally conductive PBT composite material and its preparation method, belonging to the field of polymer material processing and modification technology. Background Technology
[0002] Polybutylene terephthalate (PBT) is a thermoplastic polyester with excellent overall performance, possessing high heat resistance, fatigue resistance, self-lubricating properties, a low coefficient of friction, excellent electrical properties, and high chemical resistance. Furthermore, the symmetrical molecular structure of PBT gives it high crystallinity and good mechanical properties, making it easy to flow and mold during processing, resulting in short molding cycles and reduced production costs. PBT's outstanding overall performance and excellent price-performance ratio make it widely used in electronics, automotive parts, and machinery industries. However, PBT itself has a very low thermal conductivity, approximately 0.2 W / (m²). · K), with a high surface resistivity, greater than 10. 15 The low conductivity (Ω / sq) of PBT materials cannot meet the requirements of modern electronics industry for heat dissipation and electrical conductivity, which limits their application in heat dissipation components and electromagnetic shielding shells. Therefore, developing a PBT composite material with high electrical and thermal conductivity as well as good mechanical properties has significant industrial application value. Current research has explored improving PBT material performance by adding conductive fillers (such as conductive carbon black, graphite, carbon fiber, metal powder, metal fiber, and multi-walled carbon nanotubes) or thermally conductive fillers (such as magnesium oxide, aluminum oxide, boron nitride, and aluminum nitride). However, traditional conductive and thermally conductive fillers, due to their high proportion, negatively impact the original mechanical and processing properties of the material. Furthermore, the conductive and thermally conductive networks compete with each other, making it difficult to achieve a synergistic effect. Therefore, to obtain a PBT composite material with high electrical and thermal conductivity, it is necessary to select more efficient conductive and thermally conductive fillers, optimize the formulation system, and address the issues of competition between the conductive and thermally conductive networks and the compatibility between the filler and the matrix resin. Summary of the Invention
[0003] The purpose of this invention is to provide a PBT composite material with high electrical and thermal conductivity and its preparation method, so as to overcome the shortcomings of the prior art.
[0004] The objective of this invention is achieved through the following technical solution:
[0005] A highly conductive and highly thermally conductive PBT composite material, formulated by weight percentage from the following raw materials:
[0006] Polybutylene terephthalate (PBT) resin 40-85%,
[0007] Carbon nanostructured materials CNS1-10%,
[0008] Boron nitride 5-40%,
[0009] Alumina 5-40%,
[0010] Silane coupling agent 0.1-5%,
[0011] Dispersant 0.1-10%,
[0012] Toughening agent 1-15%,
[0013] Antioxidant 0.1-5%,
[0014] Other additives: 0-2%.
[0015] The polybutylene terephthalate (PBT) resin, under test conditions of 250°C and 2.16 kg, has a melt index >15 g / 10 min and a density of 1.28–1.32 g / cm³. 3 between.
[0016] The carbon nanostructure material CNS is an array-distributed multi-walled carbon nanotube material with a unique branched structure. Unlike traditional multi-walled carbon nanotubes (CNTs), it has a unique branched structure and better dispersibility, with a carbon content >97% and a specific surface area >200㎡ / g.
[0017] The boron nitride particles have a particle size between 10 and 40 μm and a purity > 99.5%.
[0018] The alumina is white spherical particles with a particle size between 1 and 10 μm and a purity > 99.7%.
[0019] The silane coupling agent is one or a mixture of several of KH-550, KH-560 and KH-570.
[0020] The dispersing agent is one or a mixture of several of pentaerythritol stearate, polyethylene wax, silicone, and vinyl bis-stearamide.
[0021] The toughening agent is one or a mixture of several of the following: glycidyl methacrylate-grafted ethylene-methyl acrylate copolymer, glycidyl methacrylate-grafted ethylene-butyl acrylate copolymer, glycidyl methacrylate-grafted ethylene-octene copolymer, methyl methacrylate-butadiene-styrene copolymer, and ethylene-methyl acrylate copolymer.
[0022] The antioxidants mentioned include primary antioxidants and secondary antioxidants. The primary antioxidants are hindered phenols or thioester antioxidants; the secondary antioxidants are phosphites or ester antioxidants.
[0023] The primary antioxidant is one or more of diethyl 3,5-di-tert-butyl-4-hydroxybenzyl phosphate (3114), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (1010), and octadecyl 2,β-(3,5-di-tert-butyl-4-carboxyphenyl)propionate (1076); the secondary antioxidant is one or more of triphenyl phosphite (TPP), tris(2,4-di-tert-butylphenyl) phosphite (168), and pentaerythritol diphosphite (626).
[0024] The preparation method of the high electrical and thermal conductivity PBT composite material comprises the following steps:
[0025] (1) Weigh out polybutylene terephthalate (PBT) resin, dispersant, toughening agent, antioxidant and other additives according to the above proportions, and mix them in a high-speed mixer for 2 to 5 minutes.
[0026] (2) Weigh carbon nanostructure material CNS, boron nitride, aluminum oxide and silane coupling agent according to the above proportions, and mix them in a high-speed mixer for 2 to 5 minutes to obtain a conductive and thermally conductive composite filler.
[0027] (3) Add the uniform mixture from step (1) into the main feeder of the twin-screw extruder, and at the same time add the conductive and thermally conductive composite filler corresponding to step (2) into the side feeder. After the main feeder material melts, it is melt-blended with the side feeder material and extruded and granulated. The temperatures of each section of the extruder are as follows: Zone 1 90~100℃, Zone 2 150~160℃, Zone 3 235~245℃, Zone 4 235~245℃, Zone 5 235~245℃, Zone 6 230~240℃, Zone 7 230~240℃, Zone 8 230~240℃, Zone 9 230~240℃, Zone 10 235~245℃, and the main machine speed is 400~500rpm.
[0028] This invention addresses the shortcomings of existing technologies by providing a highly conductive and thermally conductive PBT composite material and its preparation method. It involves compounding a novel dendritic carbon nanostructure material (CNS) with boron nitride / alumina and then bridging them with a silane coupling agent to form a synergistic interpenetrating conductive and thermally conductive network. This results in the PBT composite material possessing both high mechanical properties and excellent electrical and thermal conductivity, thus achieving multifunctionality for the PBT material. Detailed Implementation
[0029] The present invention can be further described through the following preferred embodiments, but these embodiments are only illustrative and do not define the scope of the present invention.
[0030] The main raw materials used in the embodiments and comparative examples of this invention are as follows:
[0031] Polybutylene terephthalate (PBT) resin: TH6100, Xinjiang Lanshan Tunhe Polyester Co., Ltd.;
[0032] Carbon nanostructure materials CNS: ATHLOS TM CNS, Cabot;
[0033] Boron nitride: BN-SS, Liaobin Fine Chemical Co., Ltd.;
[0034] Alumina: SO2, Qinhuangdao Yinuo High-tech Materials Development Co., Ltd.;
[0035] Silane coupling agent: KH-550, Boiling Point New Materials Co., Ltd.;
[0036] Dispersing agent: Pentaerythritol stearate (PETS), Osada Chemical;
[0037] Toughening agent: PTW, Dow Chemical, USA;
[0038] Primary antioxidant: 1010, Saint-Lecott;
[0039] Co-oxidant: 168, Saint-Lecott;
[0040] Carbon black: M800, Cabot;
[0041] Multi-walled carbon nanotubes: LUCAN BT1001M, LG Chem.
[0042] Example 1
[0043] 54.9 parts of polybutylene terephthalate (PBT) resin TH6100, 0.5 parts of dispersant PETS, 2 parts of toughening agent PTW, 0.2 parts of primary antioxidant 1010, 0.4 parts of secondary antioxidant 168, and 0.5 parts of carbon black M800 were added to a high-speed mixer and mixed for 2-5 minutes until homogeneous. The mixture was then fed into the main feeder of a twin-screw extruder. Simultaneously, 1 part of carbon nanostructure material CNS, 20 parts of boron nitride BN-SS, 20 parts of alumina SO2, and 0.5 parts of silane coupling agent KH-550 were weighed and added to the high-speed mixer and mixed for 2-5 minutes to obtain a conductive and thermally conductive composite filler. This filler was then added to a side feeder. After the main feeder material melted, it was melt-blended with the side feeder material, extruded, and granulated to obtain a high-conductivity and high-thermal-conductivity PBT composite material.
[0044] The temperatures of each section of the extruder are as follows: Zone 1 90-100℃, Zone 2 150-160℃, Zone 3 235-245℃, Zone 4 235-245℃, Zone 5 235-245℃, Zone 6 230-240℃, Zone 7 230-240℃, Zone 8 230-240℃, Zone 9 230-240℃, Zone 10 235-245℃. The main extruder speed is 400-500 rpm.
[0045] Example 2
[0046] 53.9 parts of polybutylene terephthalate (PBT) resin TH6100, 0.5 parts of dispersant PETS, 2 parts of toughening agent PTW, 0.2 parts of primary antioxidant 1010, 0.4 parts of secondary antioxidant 168, and 0.5 parts of carbon black M800 were added to a high-speed mixer and mixed for 2-5 minutes until homogeneous. The mixture was then added to the main feeder of a twin-screw extruder. Simultaneously, 2 parts of carbon nanostructure material CNS, 20 parts of boron nitride BN-SS, 20 parts of alumina SO2, and 0.5 parts of silane coupling agent KH-550 were weighed and added to the high-speed mixer and mixed for 2-5 minutes to obtain a conductive and thermally conductive composite filler. This filler was then added to a side feeder. After the main feeder material melted, it was melt-blended with the side feeder material, extruded, and granulated to obtain a high-conductivity and high-thermal-conductivity PBT composite material.
[0047] The temperatures of each section of the extruder are as follows: Zone 1 90-100℃, Zone 2 150-160℃, Zone 3 235-245℃, Zone 4 235-245℃, Zone 5 235-245℃, Zone 6 230-240℃, Zone 7 230-240℃, Zone 8 230-240℃, Zone 9 230-240℃, Zone 10 235-245℃. The main extruder speed is 400-500 rpm.
[0048] Example 3
[0049] 52.9 parts of polybutylene terephthalate (PBT) resin TH6100, 0.5 parts of dispersant PETS, 2 parts of toughening agent PTW, 0.2 parts of primary antioxidant 1010, 0.4 parts of secondary antioxidant 168, and 0.5 parts of carbon black M800 were added to a high-speed mixer and mixed for 2-5 minutes until homogeneous. The mixture was then fed into the main feeder of a twin-screw extruder. Simultaneously, 3 parts of carbon nanostructure material CNS, 20 parts of boron nitride BN-SS, 20 parts of alumina SO2, and 0.5 parts of silane coupling agent KH-550 were weighed and added to the high-speed mixer and mixed for 2-5 minutes to obtain a conductive and thermally conductive composite filler. This filler was then added to a side feeder. After the main feeder material melted, it was melt-blended with the side feeder material, extruded, and granulated to obtain a high-conductivity and high-thermal-conductivity PBT composite material.
[0050] The temperatures of each section of the extruder are as follows: Zone 1 90-100℃, Zone 2 150-160℃, Zone 3 235-245℃, Zone 4 235-245℃, Zone 5 235-245℃, Zone 6 230-240℃, Zone 7 230-240℃, Zone 8 230-240℃, Zone 9 230-240℃, Zone 10 235-245℃. The main extruder speed is 400-500 rpm.
[0051] Example 4
[0052] 51.9 parts of polybutylene terephthalate (PBT) resin TH6100, 0.5 parts of dispersant PETS, 2 parts of toughening agent PTW, 0.2 parts of primary antioxidant 1010, 0.4 parts of secondary antioxidant 168, and 0.5 parts of carbon black M800 were added to a high-speed mixer and mixed for 2-5 minutes until homogeneous. The mixture was then fed into the main feeder of a twin-screw extruder. Simultaneously, 4 parts of carbon nanostructure material CNS, 20 parts of boron nitride BN-SS, 20 parts of alumina SO2, and 0.5 parts of silane coupling agent KH-550 were weighed and added to the high-speed mixer and mixed for 2-5 minutes to obtain a conductive and thermally conductive composite filler. This filler was then added to a side feeder. After the main feeder material melted, it was melt-blended with the side feeder material, extruded, and granulated to obtain a high-conductivity and high-thermal-conductivity PBT composite material.
[0053] The temperatures of each section of the extruder are as follows: Zone 1 90-100℃, Zone 2 150-160℃, Zone 3 235-245℃, Zone 4 235-245℃, Zone 5 235-245℃, Zone 6 230-240℃, Zone 7 230-240℃, Zone 8 230-240℃, Zone 9 230-240℃, Zone 10 235-245℃. The main extruder speed is 400-500 rpm.
[0054] Example 5
[0055] 52.9 parts of polybutylene terephthalate (PBT) resin TH6100, 0.5 parts of dispersant PETS, 2 parts of toughening agent PTW, 0.2 parts of primary antioxidant 1010, 0.4 parts of secondary antioxidant 168, and 0.5 parts of carbon black M800 were added to a high-speed mixer and mixed for 2-5 minutes until homogeneous. The mixture was then fed into the main feeder of a twin-screw extruder. Simultaneously, 3 parts of carbon nanostructure material CNS, 10 parts of boron nitride BN-SS, 30 parts of alumina SO2, and 0.5 parts of silane coupling agent KH-550 were weighed and added to the high-speed mixer and mixed for 2-5 minutes to obtain a conductive and thermally conductive composite filler. This filler was then added to a side feeder. After the main feeder material melted, it was melt-blended with the side feeder material, extruded, and granulated to obtain a highly conductive and thermally conductive PBT composite material.
[0056] The temperatures of each section of the extruder are as follows: Zone 1 90-100℃, Zone 2 150-160℃, Zone 3 235-245℃, Zone 4 235-245℃, Zone 5 235-245℃, Zone 6 230-240℃, Zone 7 230-240℃, Zone 8 230-240℃, Zone 9 230-240℃, Zone 10 235-245℃. The main extruder speed is 400-500 rpm.
[0057] Example 6
[0058] 52.9 parts of polybutylene terephthalate (PBT) resin TH6100, 0.5 parts of dispersant PETS, 2 parts of toughening agent PTW, 0.2 parts of primary antioxidant 1010, 0.4 parts of secondary antioxidant 168, and 0.5 parts of carbon black M800 were added to a high-speed mixer and mixed for 2-5 minutes until homogeneous. The mixture was then fed into the main feeder of a twin-screw extruder. Simultaneously, 3 parts of carbon nanostructure material CNS, 30 parts of boron nitride BN-SS, 10 parts of alumina SO2, and 0.5 parts of silane coupling agent KH-550 were weighed and added to the high-speed mixer and mixed for 2-5 minutes to obtain a conductive and thermally conductive composite filler. This filler was then added to a side feeder. After the main feeder material melted, it was melt-blended with the side feeder material, extruded, and granulated to obtain a high-conductivity and high-thermal-conductivity PBT composite material.
[0059] The temperatures of each section of the extruder are as follows: Zone 1 90-100℃, Zone 2 150-160℃, Zone 3 235-245℃, Zone 4 235-245℃, Zone 5 235-245℃, Zone 6 230-240℃, Zone 7 230-240℃, Zone 8 230-240℃, Zone 9 230-240℃, Zone 10 235-245℃. The main extruder speed is 400-500 rpm.
[0060] Comparative Example 1
[0061] 52.9 parts of polybutylene terephthalate (PBT) resin TH6100, 0.5 parts of dispersant PETS, 2 parts of toughening agent PTW, 0.2 parts of primary antioxidant 1010, 0.4 parts of secondary antioxidant 168, and 0.5 parts of carbon black M800 were added to a high-speed mixer and mixed for 2-5 minutes until homogeneous. The mixture was then fed into the main feeder of a twin-screw extruder. Simultaneously, 3 parts of carbon nanostructure material CNS, 40 parts of alumina SO2, and 0.5 parts of silane coupling agent KH-550 were weighed and added to the high-speed mixer and mixed for 2-5 minutes to obtain a conductive and thermally conductive composite filler. This filler was then added to a side feeder. After the main feeder material melted, it was melt-blended with the side feeder material, extruded, and granulated to obtain a high-conductivity and high-thermal-conductivity PBT composite material.
[0062] The temperatures of each section of the extruder are as follows: Zone 1 90-100℃, Zone 2 150-160℃, Zone 3 235-245℃, Zone 4 235-245℃, Zone 5 235-245℃, Zone 6 230-240℃, Zone 7 230-240℃, Zone 8 230-240℃, Zone 9 230-240℃, Zone 10 235-245℃. The main extruder speed is 400-500 rpm.
[0063] Comparative Example 2
[0064] 52.9 parts of polybutylene terephthalate (PBT) resin TH6100, 0.5 parts of dispersant PETS, 2 parts of toughening agent PTW, 0.2 parts of primary antioxidant 1010, 0.4 parts of secondary antioxidant 168, and 0.5 parts of carbon black M800 were added to a high-speed mixer and mixed for 2-5 minutes until homogeneous. The mixture was then fed into the main feeder of a twin-screw extruder. Simultaneously, 3 parts of multi-walled carbon nanotubes LUCAN BT1001M, 20 parts of boron nitride BN-SS, 20 parts of alumina SO2, and 0.5 parts of silane coupling agent KH-550 were weighed and added to the high-speed mixer and mixed for 2-5 minutes to obtain a conductive and thermally conductive composite filler. This filler was then added to a side feeder. After the main feeder material melted, it was melt-blended with the side feeder material, extruded, and granulated to obtain a highly conductive and thermally conductive PBT composite material.
[0065] The temperatures of each section of the extruder are as follows: Zone 1 90-100℃, Zone 2 150-160℃, Zone 3 235-245℃, Zone 4 235-245℃, Zone 5 235-245℃, Zone 6 230-240℃, Zone 7 230-240℃, Zone 8 230-240℃, Zone 9 230-240℃, Zone 10 235-245℃. The main extruder speed is 400-500 rpm.
[0066] Performance evaluation and implementation standards:
[0067] In the above embodiments and comparative examples, the performance of the products was tested according to the following standards and conditions.
[0068] Apparent density was tested according to ISO 1183-1; flexural strength and flexural modulus were tested according to ISO 178, with a specimen size of 80×10×4mm, a bending speed of 2mm / min, and a span of 64mm; tensile strength was tested according to ISO 527, with a type 1A specimen and a tensile speed of 5mm / min; notched impact strength of simply supported beams was tested according to ISO 179-1, with a specimen size of 80×10×4mm, a type A notch, and a test temperature of 23℃; surface resistivity was tested according to ASTM D257; and thermal conductivity was tested according to GB / T 10295.
[0069] The test results of various physical properties of the products obtained in Examples 1-6 and Comparative Examples 1-2 are listed in Table 1.
[0070] As shown in Table 1, the thermal conductivity of the PBT composite materials obtained in Examples 2-6 is all greater than 0.9 W / (m²). · K), the surface resistivity can reach 10. 4 The surface resistivity of the PBT composite material is below Ω / sq, and it exhibits excellent mechanical properties, with high flexural strength, flexural modulus, tensile strength, and notched impact strength. Furthermore, comparative studies of Examples 1-4 show that increasing the amount of carbon nanostructured material (CNS) continuously reduces the surface resistivity of the PBT composite material, reaching a minimum of 10 Ω / sq. 2 The Ω / sq value shows that the flexural strength, flexural modulus, and tensile strength are continuously improved. This indicates that the present invention has effectively solved the compatibility problem between thermally conductive and electrically conductive fillers and matrix resin, while also enabling a synergistic effect between the conductive and thermally conductive fillers.
[0071] Comparing Examples 3, 5, and 6 with Comparative Example 1, it can be seen that adding a single conductive filler, spherical alumina, results in a product with a lower thermal conductivity (<0.6 W / (m²)). · While boron nitride (BN) has relatively poor rigidity, the combination of boron nitride and spherical alumina exhibits a synergistic effect, facilitating the formation of a thermally conductive network within the material system. With the same total addition ratio, the thermal conductivity of the product obtained from the combination of boron nitride and spherical alumina is greater than 0.9 W / (m²). · K). Comparing Example 3 with Comparative Example 2, it can be found that, with the same amount of addition, carbon nanostructure material CNS has a much better electrical conductivity than conventional multi-walled carbon nanotube material CNT. Moreover, CNS is more likely to have a synergistic effect with thermally conductive fillers. With the same formulation, the thermal conductivity, tensile strength, flexural strength, flexural modulus and notched impact strength of the product with added CNS are significantly higher than those of the product with the same proportion of CNT.
[0072] This invention provides a PBT composite material with high electrical and thermal conductivity. This composite material has excellent electrical conductivity, high thermal conductivity, and excellent mechanical properties, and is suitable for electronic components, electromagnetic shielding, and automotive parts.
[0073] Table 1. Physical properties of the corresponding products in the examples and comparative examples.
[0074]
[0075] The above embodiments are provided to better illustrate the specific content of the present invention, but the scope of protection of the present invention is not limited thereto. Any researcher skilled in the art can easily modify or replace these embodiments and apply the basic principles of the present invention to other embodiments without creative effort. Therefore, the scope of protection of the present invention should be determined by the scope defined in the claims.
Claims
1. A high conductive, high thermal conductive PBT composite material, characterized in that, By weight percent, prepared from the following raw materials: Polybutylene terephthalate (PBT) resin 40-85%, Carbon nanostructure material CNS 1-10%, Boron nitride 5-40%, Alumina 5-40%, Silane coupling agent 0.1-5%, Dispersion aid 0.1-10%, Toughening agent 1-15%, Antioxidant 0.1-5%, Other aids 0-2%.
2. The high-conductivity, high-thermal-conductivity PBT composite material according to claim 1, characterized in that, The polybutylene terephthalate (PBT) resin has a melt index of > 15 g / 10 min at 250°C under a test condition of 2.16 kg, and a density of 1.28-1.32 g / cm 3 .
3. The high-conductivity, high-thermal-conductivity PBT composite material according to claim 1, characterized in that, The carbon nanostructure material CNS is a multi-walled carbon nanotube material with unique bifurcated structure and array distribution, which has unique branch structure and better dispersibility, carbon content > 97%, specific surface area > 200 m2 / g.
4. The high-conductivity, high-thermal-conductivity PBT composite material according to claim 1, characterized in that, The particle size of the boron nitride is between 10-40 μm, and the purity is > 99.5%.
5. The high-conductivity, high-thermal-conductivity PBT composite material according to claim 1, characterized in that, The alumina is white spherical particles with a particle size of 1-10 μm and a purity of > 99.7%.
6. The high-conductivity, high-thermal-conductivity PBT composite material according to claim 1, characterized in that, The silane coupling agent is one or a mixture of several of KH-550, KH-560 and KH-570.
7. The high-conductivity, high-thermal-conductivity PBT composite material according to claim 1, characterized in that, The dispersion aid is one or a mixture of several of pentaerythritol stearate, polyethylene wax, silicone, and vinyl bis-stearamide.
8. The high-conductivity, high-thermal-conductivity PBT composite material according to claim 1, characterized in that, The toughening agent is one or a mixture of several of glycidyl methacrylate grafted ethylene-methyl acrylate copolymer, glycidyl methacrylate grafted ethylene-butyl acrylate copolymer, glycidyl methacrylate grafted ethylene-octene copolymer, methyl methacrylate-butadiene-styrene copolymer, and ethylene-methyl acrylate copolymer.
9. The high-conductivity, high-thermal-conductivity PBT composite material according to claim 1, characterized in that, The antioxidant includes primary antioxidant and auxiliary antioxidant, the primary antioxidant is hindered phenol or sulfur ester antioxidant; the auxiliary antioxidant is phosphite or ester antioxidant.
10. The high-conductivity, high-thermal-conductivity PBT composite material according to claim 9, characterized in that, The primary antioxidant is one or several of 3,5-di-tert-butyl-4-hydroxybenzyl diethyl phosphate (3114), tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] pentaerythritol ester (1010), and 2,β-(3,5-di-tert-butyl-4-carboxyphenyl)propyl octadecyl ester (1076); the auxiliary antioxidant is one or several of triphenyl phosphite (TPP), tris(2,4-di-tert-butylphenyl) phosphite (168), and bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite (626).
11. The process for preparing the high-conductivity, high-thermal-conductivity PBT composite material according to any one of claims 1-10, characterized in that, The steps are as follows: (1) Weigh the polybutylene terephthalate (PBT) resin, dispersion aid, toughening agent, antioxidant and other aids according to the above proportions, and mix in a high-speed mixer for 2-5 min; (2) Weigh the carbon nanostructure material CNS, boron nitride, alumina and silane coupling agent according to the above proportions, and mix in a high-speed mixer for 2-5 min to obtain a conductive and thermal conductive composite filler; (3) the uniform mixture in step (1) is added into the main feeder of the twin-screw extruder, while the corresponding conductive and heat-conductive composite filler in step (2) is added into the side feeder, and after the main feeding material is melted, the materials from the side feeding are melt blended and extruded and granulated, the temperature of each section of the extruder is as follows: zone 1 90-100℃, zone 2 150-160℃, zone 3 235-245℃, zone 4 235-245℃, zone 5 235-245℃, zone 6 230-240℃, zone 7 230-240℃, zone 8 230-240℃, zone 9 230-240℃, zone 10 235-245℃, and the rotation speed of the main machine is 400-500 rpm.